EVALUATION OF DRAINAGE CHANNEL PERFORMANCE ON CLOVE FLOWER STREET : Evaluasi Kinerja Saluran Drainase pada Jalan Bunga Clove - Buton, Suriyani; Muharyanto, Eddy Agus (Uniqbu Journal of Exact Sciences, 2021)
Namlea Village is one of the villages in Maluku Province, Buru Regency, currently developing in terms of economy and population growth. Land-use changes have an impact on soil infiltration, with the amount of surface runoff which has the potential for flooding at several points to become a problem in Namlea Village, significant surface runoff on the clove flower road causes the drainage channel on the road to be unable accommodate the discharge of water that enters the drain. This research was conducted by referring to primary data and secondary data. Primary data, data obtained by conducting field surveys (research places/locations), while secondary data, data obtained directly from related agencies as supporting data in the final project writing. This. The planning analysis results with rainfall data taken from the BMKG (Meteorology, Climatology and Geophysics Agency). By paying attention to the hydrological design criteria table for the urban drainage planning system, appendix 8 and the data on water users in table 4.12 and population density projection data for 2015 taken from the statistical agency. Then the results of our planning analysis take a maximum plan age of 2 years with a maximum rainfall = 410,907 mm, with a planned discharge due to rainwater runoff Qp = 1,167 m3 / s and release due to household waste Qlimbah = 0.0025 m3 / s, then the total discharge Qtotal = 1.1695 m3 / s, with the results of the above analysis, the existing channel capacity is unable to accommodate water discharge due to rainfall or burst due to household waste because the current channel discharge is only able to accommodate a release of Q = 0.44 m3 / s with a volume capacity of V = 209,375 m3, while the volume capacity of the channel on Jalan Bunga Cengkeh is following the current population density and must be able to accommodate a discharge of Qtotal = 1.1695 m3 / s. With an average annual volume capacity of V = 25612.05 m3. The existing channel dimensions must be rehabilitated according to the planning analysis results that the author had planned with a trapezoidal channel cross-section. Keywords: Evaluation of drainage channels, channel capacity, due to rainwater discharge